Pendampingan Edukasi Manasik Umrah (EduManarah) untuk Peningkatan Kualitas Spiritual - Setiawan, Eko; KH, Humaidi (LPPM Universitas KH. A. Wahab Hasbullah, 2026)
The limited understanding of prospective umrah pilgrims, particularly in Batu City, serves as the background of this community service activity. The understanding of prospective pilgrims should not only focus on technical aspects but also encompass deeper spiritual dimensions. Based on preliminary observations in Batu City, some participants were still primarily focused on procedural aspects without fully comprehending the spiritual meaning of the worship. Therefore, this activity aims to enhance participants’ understanding, improve the quality of worship, and strengthen spiritual awareness through educational mentoring in umrah rituals. The methods employed include material socialization, direct practice of manasik umrah, and intensive participatory mentoring. This activity involved partner groups of prospective umrah pilgrims from the “ESJE Group,” consisting of PT. Shahin Jaya and PT. My Hidayah. During the mentoring process, participants were not only trained in the proper procedures but were also encouraged to reflect on the spiritual values embedded in each stage of the worship. The results indicate an improvement in participants’ understanding of proper umrah practices in accordance with religious guidelines, as well as increased awareness of the importance of intention, devotion, and closeness to Allah. Participants’ enthusiasm was also evident through their active involvement in discussions and practical sessions. Thus, this mentoring activity has had a positive impact in preparing pilgrims more comprehensively, both in terms of knowledge and spiritual readiness.